Effect of Rhizobium and Molybdenum on Growth, Root Nodulation and Yield of Mung Bean (Vigna radiata L.) in Tikapur, Kailali - Awasthi, Laxmi Kumari; Pandey, Lalit; Chalise, Devraj (Journal of Tikapur Multiple Campus, 2025)
A field experiment was conducted at Agronomy farm of Far Western University, School of Agriculture, Tikapur, Kailali during spring season of 2024 to study the effect of Rhizobium and molybdenum on growth, root nodulation and yield of mung bean. The trial was laid out in two factorial randomized complete block design having four replications and six treatments. Two levels of Rhizobium (with and without) and three levels of molybdenum (0, 1 and 2 kg ha-1) were used. Sodium molybdate as a source of molybdenum and seeds of variety SML-668 were used. The experimental results revealed that application of Rhizobium + 2 kg ha-1 molybdenum provided significantly higher plant height (54.84 cm), root length (17.03 cm), total nodules (21), effective nodules (18), fresh weight of root (2.33 g), dry weight of root (1.02 g), root volume (2.43 ml), fresh weight of shoot (65.18 g), pod length (8.97 cm), seeds/pod (10), pods/plant (34) followed by Rhizobium + 1 kg ha-1 molybdenum. Similarly, number of branches/plant (13), grain yield (1.7ton ha-1), biomass yield (6.71ton ha-1) and 1000 grain weight (51.45 g) also recorded highest at Rhizobium + 2 kg ha-1 molybdenum. The effect of sole Rhizobium inoculation and increasing level of molybdenum was significant over control for all these parameters. Number of effective nodules was positively correlated with all the growth, yield and yield attributing parameters with concluding Rhizobium + 2 kg ha-1 molybdenum as best combination for growth, root nodulation and yield of mung bean in Tikapur, Kailali.